Structure and function: how to design integrated anatomy and physiology modules for the gross anatomy laboratory - Allison, Sara; Mueller, Caroline; Lackey-Cornelison, Wendy (Frontiers in Physiology, 2023)
Physicians must be able to integrate knowledge across disciplines. Therefore, educators need to provide opportunities for students to cognitively integrate information across the medical school curriculum. Literature has shown that specifically pointing out these connections helps students create cause and effect models and ultimately improve their performance. The gross anatomy laboratory provides an excellent environment for students to integrate information by establishing structure and function relationships. This article presents simple steps to create modules which help students cognitively integrate physiology and anatomy at the session level in the gross anatomy laboratory. Driven by backward design, these steps include establishing objectives, creating assessments, and developing activities that can be implemented in a specific learning environment. An example of a flexible module which could be implemented in a number of gross anatomy lab settings (e.g., prosection, dissection, models, virtual) is presented along with a template for the design of future modules. This is followed by a discussion of challenges encountered by educators attempting to integrate structure and function in the gross anatomy lab. Each of these considerations will be addressed with potential solutions for educators seeking to implement these types of integrated activities.